New Issues and Old Struggles: The Evolving Rights of Filipino Overseas Migrants - Tigno, Jorge V. (Philippine Social Sciences Review; The Revolution of 1896 and the Continuing Struggle for National Dignity and Solidarity, Ed., Gil G. Gotiangco, 2010)
The Filipino struggle for human dignity and sovereignty continues as illustrated by the extent to which the rights of innumerable workers now employed and living overseas are being violated. The paper will attempt to outline the evolution of the human rights of Filipino migrants overseas culminating in the formulation of the Overseas Filipinos and Migrant Workers Act of 1995 (Republic Act No. 8042). It will also describe the extent of human rights violations against migrant workers or overseas contract workers (OCWs) by receiving governments. Particular case studies would be domestic workers going to Singapore and Hongkong as well as entertainment workers going to Japan. In addition, the paper will try to trace the involvements of NGOs and POs in advocating the rights and welfare of Filipinos overseas and their families. The paper will argue that the difficulties encountered by Filipino revolutionaries at the turn of the century are the same problems confronting human rights advocates in the Philippines, namely that human rights advocacy must necessarily confront the powers of sovereign states including the restrictive economies of receiving countries.